2016
DOI: 10.14311/asfe.2015.031
|View full text |Cite
|
Sign up to set email alerts
|

Deflection Response of Reinforced Concrete Slabs Tested in Punching Shear in Fire

Abstract: Flat slab-column punching shear specimens were tested under combined load and fire exposure, with varying edge restraint conditions. The slabs deflected away from the heat source (in the direction of loading) at all stages of the tests. This paper examines this unusual deflection behaviour, although no definitive reason for this unexpected behaviour has been found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…In all the above tests, and most clearly documented by Smith et al [4][5][6][7], the deflections of the slabs when heated was in the opposite direction to that expected by the experimentalists ( Figure 2). A simple thermo-mechanical analysis suggests that when heated as described, deflections of Smith's slabs due to thermal expansion would be towards the heating source.…”
Section: Introductionsupporting
confidence: 49%
See 2 more Smart Citations
“…In all the above tests, and most clearly documented by Smith et al [4][5][6][7], the deflections of the slabs when heated was in the opposite direction to that expected by the experimentalists ( Figure 2). A simple thermo-mechanical analysis suggests that when heated as described, deflections of Smith's slabs due to thermal expansion would be towards the heating source.…”
Section: Introductionsupporting
confidence: 49%
“…plus transient thermal strain (tts) (dashed lines). It was found that simply introducing elevated temperatures together with the above material properties to the ambient temperature model was not sufficient to reproduce Smith's [4][5][6] experimental results ( Figure 10). Instead, a response as might be expected from a simple consideration of thermal expansion was seen, as in Figure 2.…”
Section: Elevated Temperature Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…One important point to note from Liao et al [4] is that the slabs heated on the compression side showed the same unexpected deflection behaviour noted first by Kordina [1,2]. Subsequent to the aforementioned work, Smith et al [5][6][7][8] investigated slab-column connection behaviour under fire. They used 16 specimens of dimension 1400 x 1400 mm and depths of 50, 75 and 100mm; five of which were tested at ambient temperature to determine their punching shear resistance.…”
Section: Introductionmentioning
confidence: 87%
“…Figure 2 The load deflection profile for specimens (a) for A, B and (b) for C, based on Kordina [1,2] Similarly, Smith et al [5][6][7][8] implemented an LR of (70-80%) in all of the tested slabs and the deflection reported was again moving away from the heating source.…”
Section: Background and Motivationmentioning
confidence: 99%